2010
DOI: 10.1021/ja1022267
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Remote-Controlled Release of Drug Molecules in Vitro Using Magnetic Actuation of Mechanized Nanoparticles

Abstract: Mesoporous silica nanoparticles are useful nanomaterials that have demonstrated the ability to contain and release cargos with mediation by gatekeepers. Magnetic nanocrystals have the ability to exhibit hyperthermic effects when placed in an oscillating magnetic field. In a system combining these two materials and a thermally sensitive gatekeeper, a unique drug delivery system can be produced. A novel material that incorporates zinc-doped iron oxide nanocrystals within a mesoporous silica framework that has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
503
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(508 citation statements)
references
References 40 publications
4
503
0
1
Order By: Relevance
“…With a gradually increase in studies, a series of MSN-based stimuli-responsive systems have been reported. 34,35 The drug release is subsequently to be triggered by environmental stimuli including physical signals (eg, temperature, 36,37 electricity, 38 magnetic field, 39 and photons [40][41][42] ) and chemical signals (eg, pH values, 43 redox potential, [44][45][46] and enzymatic activities 47,48 ). In this review, we intend to discuss about the advanced progress related to MSN for drug delivery associated with special focus on environmental responsive mechanisms and highlight the effect of endogenous stimuli in drug delivery such as pH, redox, enzyme, ATP, glucose, and H 2 O 2 , as well as exogenous stimuli including thermo, light, ultrasound, and magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a gradually increase in studies, a series of MSN-based stimuli-responsive systems have been reported. 34,35 The drug release is subsequently to be triggered by environmental stimuli including physical signals (eg, temperature, 36,37 electricity, 38 magnetic field, 39 and photons [40][41][42] ) and chemical signals (eg, pH values, 43 redox potential, [44][45][46] and enzymatic activities 47,48 ). In this review, we intend to discuss about the advanced progress related to MSN for drug delivery associated with special focus on environmental responsive mechanisms and highlight the effect of endogenous stimuli in drug delivery such as pH, redox, enzyme, ATP, glucose, and H 2 O 2 , as well as exogenous stimuli including thermo, light, ultrasound, and magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Many other temperature-sensitive materials are also used as gatekeepers, such as lipid bilayer 155 and pseudorotaxanes, 39 and the heat generated from alternating magnetic field induced the disassembly of the blockers and sustained drug release.…”
mentioning
confidence: 99%
“…In fact, a nanovalve system was perfectly designed by combining controlled drug release ability of mesoporous nanoparticles with hyperthermic effect of MNPs, wherein zinc-doped iron oxide nanoparticles were encapsulated within mesoporous silica shells and subsequently cyclic cucurbituril was used for capping the pores. [360] Interestingly, upon exerting an oscillating magnetic field, the electrostatically bound nanovalve molecules were removed by the induced heat generated by incorporated magnetic nanoparticles, and resulted in cargo release.…”
Section: Silicamentioning
confidence: 99%
“…7 Furthermore, release of anticancer drugs loaded into magnetic core silica nanoparticles can be controlled by an external magnetic field. 8 Hydrogel nanoparticles (or nanogels) were developed to protect and transport siRNA into diseased cells via the intravenous route. 9 For image-guided cancer surgery, a near-infrared emitting polymer nanogel was efficient enough to map sentinel lymph nodes, which cancer cells are most likely to migrate to from a primary site.…”
Section: Applications Of Multifunctional Nanoparticles In Biomedicinementioning
confidence: 99%